Covering the '60s / George Lois the Esquire Era - Lois George (The Monacelli Press, 1996)
Mom & Pop Culture, My Lonely War Protest, Heroes and Anti-Heroes, Debunkers, Women (with a Vengeance), Athletes - The Agony and the Ecstasy, Joe's Boys, Good and Bad Nostalgia, Morality, Martyrs, My Reluctant Pinups, Race.
Mom & Pop Culture, My Lonely War Protest, Heroes and Anti-Heroes, Debunkers, Women (with a Vengeance), Athletes - The Agony and the Ecstasy, Joe's Boys, Good and Bad Nostalgia, Morality, Martyrs, My Reluctant Pinups, Race.